The diagnostic value of p63, p16, and p53 immunohistochemistry in distinguishing seborrheic keratosis, actinic keratosis, and Bowen's disease. Issue 2 (8th February 2021) - Nasiri, Soheila; Azhari, Vahidehsadat; Bidari‐Zerehpoosh, Farahnaz; Asadi‐Kani, Zahra; Talebi, Atefeh
Abstract: Seborrheic keratosis (SK), actinic keratosis (AK), and Bowen's disease (BD) are squamoproliferative disorders of the skin. Histologically, they may mimic each other and therefore, they might be misinterpreted, especially in small samples. The aim of this study is to clarify the expression of p63, p16, and p53 proteins in SK, AK, and BD and evaluate the efficacy of these markers in order to distinguish between the aforementioned lesions. A total of 46 cases were collected (15 SK, 16 AK, and 15 BD) and stained for p63, p16, and p53. The stain intensity and the cell distribution labeling were scored and then analyzed by SPSS software. All cases of BD which became positive for p53 revealed basal keratinocytes sparing. Instead, all or nearly all basal keratinocytes in AK cases were positive for this marker. These were also seen in p16 staining results and they were between AK and BD ( P = .024). Our study demonstrates p16 and p53 are useful markers in separating AK and BD according to basal keratinocytes involvement and sparing, respectively.